Usp7 contributes to the tail regeneration of planarians via Islet/Wnt1 axis - Ang Liang; Jinglong Liu; Zhiyuan Zhang; Jing Xiao; Dezeng Liu; Zimei Dong; Guangwen Chen (Journal of Translational Medicine)
Abstract Background Regeneration plays a key role in energy recycling and homeostasis maintenance. Planarians, as ideal model animals for studying regeneration, stem cell proliferation, and apoptosis, have the strong regenerative abilities. Considerable evidence suggests that ubiquitin plays an important role in maintaining homeostasis and regulating regeneration, but the function of Ubiquitin specific proteases 7 (Usp7) on regeneration in planarians remains elusive. Methods We identified an evolutionarily conserved gene, Usp7, and utilized RNA interference (RNAi), Quantitative real-time PCR (qRT-PCR), Whole-mount immunofluorescence, Tunnel, Whole-mount in situ hybridization (WISH), and western blotting to detect the function of Usp7 during the planarian regeneration. Results In this study, we found that the regenerative trunk fragments in the Usp7 RNAi worms could not regenerate missing tails; meanwhile, the level of cell proliferation was decreased, while cell apoptosis was increased. Furthermore, the expression of Islet was inhibited in the Usp7 RNAi worms during planarian regeneration. The hybridization signal of wnt1/P-1 exhibited the dot-like pattern at the posterior of the regenerating planarians after Usp7 RNAi at regenerative 1 day (R 1 d). However, the concentrated expression pattern wnt1/P-1 dramatically declined at regenerative 3 days (R 3 d) and disappeared at regenerative 7 days (R 7 d). In addition, activating the Wnt pathway partially rescued regenerative defects induced by inhibition of Usp7. Conclusions Collectively, Usp7 is necessary for tissue regeneration and tail blastema formation partially by regulating the cell proliferation and apoptosis during planarian regeneration. It could also promote the posterior polarity reconstruction of the regenerative planarians via the Islet/Wnt1 axis.